1995
DOI: 10.1002/dir.4000090307
|View full text |Cite
|
Sign up to set email alerts
|

Direct marketing and the use of individual-level consumer information: Determining how and when “privacy” matters

Abstract: The desire to maximize marketing effectiveness and reduce communication costs has increased direct marketers' reliance on computerized databases, customized persuasion, and other consumer information intensive strategies and tactics (28,541. The belief that the success of marketing efforts is positively related to the amount and specificity of individual-level consumer information (7). however, has raised questions about how far companies should be allowed to go in learning about or attempting to persuade cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 16 publications
(13 reference statements)
1
122
0
2
Order By: Relevance
“…When online agents ask permission to collect information or disclose that they will be collecting information consumers become aware that information about them is being or will be collected. Research has shown that privacy concerns tend to be reduced when permission is obtained (Nowak and Phelps, 1995) and heightened when consumers discover information was collected without their awareness (Cespedes and Smith, 1993). This aspect of privacy concerns relates closely to what Palmer (2005) calls ''questions of technique'' -without permission or disclosure (neither of which are routinely practiced) information can be collected in a way that consumers can neither avoid nor detect.…”
Section: Legislative Responsesmentioning
confidence: 97%
See 3 more Smart Citations
“…When online agents ask permission to collect information or disclose that they will be collecting information consumers become aware that information about them is being or will be collected. Research has shown that privacy concerns tend to be reduced when permission is obtained (Nowak and Phelps, 1995) and heightened when consumers discover information was collected without their awareness (Cespedes and Smith, 1993). This aspect of privacy concerns relates closely to what Palmer (2005) calls ''questions of technique'' -without permission or disclosure (neither of which are routinely practiced) information can be collected in a way that consumers can neither avoid nor detect.…”
Section: Legislative Responsesmentioning
confidence: 97%
“…This dimension of control is often discussed in relation to permission and disclosure (e.g. Cespedes and Smith, 1993;Nowak and Phelps, 1995). When online agents ask permission to collect information or disclose that they will be collecting information consumers become aware that information about them is being or will be collected.…”
Section: Legislative Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…A customer's sensitivity to revealing distinct types of personal information differs from one to the next, generating a wide range of privacy concerns [47]. Phelps et al [54] identify 5 data typologies: socio-demographic, lifestyle, buying and consumption habits, financial, and personal identification, considering the last two as particularly sensitive from the customer's point of view.…”
Section: Sensitivity To the Information Requested Of A Customermentioning
confidence: 98%